FORMAÇÃO INICIAL DE PROFESSORES COM ÊNFASE NA GESTÃO DA EDUCAÇÃO: UMA ANÁLISE NOS CURSOS DE LICENCIATURA EM PEDAGOGIA DA UNIVERSIDADE ESTADUAL DO CENTRO-OESTE - CAMPI GUARAPUAVA E IRATI - GURA, VANDERLÉIA (2020)
This research has as aim at analyzing the proposal and working of degree course in Pedagogy of the Midwestern State University - Campi Guarapuava and Irati/PR (2006/2019) in order to identify how the initial training content deals with the referral for work with school management. Thereunto, researchers carried out on initial training policies were contextualized with the objective to delimit the specificity proposed to investigate and their possible contributions. The text present historical influences in teachers training, as well as policies formulation and conception of State. The training process of school manager was characterized in the degree course of Pedagogy investigating the public policies of teacher training. A study was performed on the National Curricular Guidelines for the Pedagogy Course from the Resolution CNE/CP number 1, 15th May, 2006 and the transition to the Resolution CNE/CP number 2, 9th June, 2015, from what define the National Curriculum Guidelines for initial and continuing training. The study also deals with the analysis of the Course Pedagogical Projects (PPCs in Portuguese acronym), specifically the Curriculum Matrices and the Subject programs which deal with the pedagogue training to work with school management. Teachers of the degree course of Pedagogy was interviewed in both campi in order to verify and analyzing how the policy are conceived, interpreted and practiced. As theoretical-methodological referential, the policy cycle approach was used through its three first contexts: influence, text production and practice, enabling the interpretation of public policies for teacher initial training. As main findings within the path, it was possible conclude there is a gap regarding the research that deal specifically with initial training of the managing pedagogue. Regarding the initial teacher training policies, there was several discussions, presenting relevant major changes in the field. Regarding Curriculum matrices of the campi Guarapuava and Irati, they indicate follow macro level standards, but each campus specifies some type of weakness.